2019
DOI: 10.1016/j.gca.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Strange messenger: A new history of hydrogen on Earth, as told by Xenon

Abstract: Atmospheric xenon is strongly mass fractionated, the result of a process that apparently continued through the Archean and perhaps beyond. Previous models that explain Xe fractionation by hydrodynamic hydrogen escape cannot gracefully explain how Xe escaped when Ar and Kr did not, nor allow Xe to escape in the Archean. Here we show that Xe is the only noble gas that can escape as an ion in a photo-ionized hydrogen wind, possible in the absence of a geomagnetic field or along polar magnetic field lines that ope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
149
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 148 publications
(155 citation statements)
references
References 109 publications
5
149
1
Order By: Relevance
“…The corollary is that the halogen/seawater ratio remained constant within ~20-30% from 3.5 Ga to present, implying that the potential escape of hydrogen from photodissociation of atmospheric H2O might have been limited. A ~30% water loss is consistent with modeling of the escape of atmospheric xenon which requires approximately this amount of oceanic water to be dissociated and resulting hydrogen to be lost into space in order to lift up Xe ions(Zahnle et al 2019).…”
supporting
confidence: 77%
See 3 more Smart Citations
“…The corollary is that the halogen/seawater ratio remained constant within ~20-30% from 3.5 Ga to present, implying that the potential escape of hydrogen from photodissociation of atmospheric H2O might have been limited. A ~30% water loss is consistent with modeling of the escape of atmospheric xenon which requires approximately this amount of oceanic water to be dissociated and resulting hydrogen to be lost into space in order to lift up Xe ions(Zahnle et al 2019).…”
supporting
confidence: 77%
“…If hydrogen originated from the photo-dissociation of H2O vapor, its escape could have resulted in change on the volume and composition of the hydrosphere. Zahnle et al (2019) suggested that a volume of water corresponding to about 30 % of the present oceans could have escaped although this amount would be overestimated if Xe escape happened in short and intense episodes. Alternatively, hydrogen could have originated from CH4 dissociation (Catling et al 2001).…”
Section: Escape Models and Research Avenuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our calculations assumes all NOX entering the ocean goes to NOX and neglects reactions of NOX with other reductants which may have been abundant on early Earth, such as H 2 , CH 4 , or Mn 2+ (Fischer et al, ; Tian et al, ; Zahnle et al, ). Consequently, our estimates should be considered upper bounds on prebiotic [ NOX].…”
Section: Discussionmentioning
confidence: 99%